2020
DOI: 10.1136/bmjdrc-2020-001569
|View full text |Cite
|
Sign up to set email alerts
|

Performance and costs of multiple screening strategies for type 2 diabetes: two population-based studies in Shanghai, China

Abstract: IntroductionTo compare the performance and the costs of various assumed screening strategies for type 2 diabetes mellitus (T2DM) among Chinese adults, and identify an optimal one for the population.Research design and methodsTwo multistage-sampling surveys were conducted in Shanghai, China, in 2009 and 2017. All participants were interviewed, had anthropometry, measured fasting plasma glucose (FPG), hemoglobin A1c (A1c) and/or postprandial glucose. The 1999 WHO diagnostic criteria was used to identify undiagno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Suggested strategies for screening T2DM include fasting plasma glucose and HbA1c, diabetes risk assessment using the DRS scale and various questionnaires, as well as a combination of the given strategies. A study conducted in Shanghai, China, demonstrated the feasibility of screening for T2DM by assessing fasting plasma glucose levels in the adult population (28). The authors' specific risk assessment system included the data on age, sex, BMI, WC, systolic BP, and family history of T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…Suggested strategies for screening T2DM include fasting plasma glucose and HbA1c, diabetes risk assessment using the DRS scale and various questionnaires, as well as a combination of the given strategies. A study conducted in Shanghai, China, demonstrated the feasibility of screening for T2DM by assessing fasting plasma glucose levels in the adult population (28). The authors' specific risk assessment system included the data on age, sex, BMI, WC, systolic BP, and family history of T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…BP was measured on the right arm in the sitting position using standard mercury sphygmomanometer after at least 5‐min rest 17 . The interval of two BP measurements was at least 2 min and the mean was used in data analysis 15,18,19 . Body mass index (BMI) was calculated as body weight in kilograms divided by standing height in meters squared (kg/m 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…17 The interval of two BP measurements was at least 2 min and the mean was used in data analysis. 15,18,19 Body mass index (BMI) was calculated as body weight in kilograms divided by standing height in meters squared (kg/m 2 ).…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The details of the three surveys using multistage stratified sampling procedure were described in our previous reports 18 , 19 , 20 . Briefly, a representative sample of the general population was randomly selected through a multistage sampling process in the 2002–2003 survey.…”
Section: Methodsmentioning
confidence: 99%